APLIKASI MEDIA PEMBELAJARAN SMART QUIZ GAME BERBASIS ANDROID MENGGUNAKAN METODE COGRUENTIAL GENERATOR UNTUK (SD) SEKOLAH DASAR - Dilani Tri Ovandi; Sofa Sofiana (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
This quiz application is a quiz application that has an element of learning in smartphones with this game that can provide learning as well as entertainment for its users, and can provide learning as well as insight into PPKN science, a quiz is a game or a player's mind in solving a quiz game, where the player (as in a group / team or individually) the player tries to answer the questions in the game quiz in order to achieve the goal or get the highest score / score in the game so that the user is forced to think about answering the questions in the game. The method used in the game quiz application is the Linear Congruential Generator (LCG) method and the String Maching (SM) method, the LCG method functions to randomize the questions in the application by random, the Sring Maching (SM) method is used for matching questions. on the answers in the application with the selected answer to the question "true and false".